Knit one, kill two eaudiobook - Sefton, Maggie (Knitting Mystery, 2010)
Unabridged, 9 hours Read by Jane Jacobs Despite the fact that her aunt was an expert knitter, Kelly Flynn never picked up a pair of knitting needles she liked-until she strolled into House of Lambspun. Now, in the first in a brand-new series, she learns how to knit one, purl two, and untangle the mystery behind her aunt's murder...